Efficient passivation of n-type and p-type silicon surface defects by hydrogen sulfide gas reaction. (3rd September 2021) - Das, U K; Theisen, R; Hua, A; Upadhyaya, A; Lam, I; Mouri, T K; Jiang, N; Hauschild, D; Weinhardt, L; Yang, W; Rohatgi, A; Heske, C
Abstract: An efficient surface defect passivation is observed by reacting clean Si in a dilute hydrogen sulfide–argon gas mixture (<5% H2 S in Ar) for both n-type and p-type Si wafers with planar and textured surfaces. Surface recombination velocities of 1.5 and 8 cm s −1 are achieved on n-type and p-type Si wafers, respectively, at an optimum reaction temperature of 550 °C that are comparable to the best surface passivation quality used in high efficiency Si solar cells. Surface chemical analysis using x-ray photoelectron spectroscopy shows that sulfur is primarily bonded in a sulfide environment, and synchrotron-based soft x-ray emission spectroscopy of the adsorbed sulfur atoms suggests the formation of S–Si bonds. The sulfur surface passivation layer is unstable in air, attributed to surface oxide formation and a simultaneous decrease of sulfide bonds. However, the passivation can be stabilized by a low-temperature (300 °C) deposited amorphous silicon nitride (a-Si:N X :H) capping layer.